A New Anthropometric Instrument for Inclination Measurements of Face and Its Reliability - Ögetürk, Murat (Fırat University, 2005)
Objectives: Anthropometry is widely recognized as an important method in the evaluation of dysmorphic faces. Inclination measurements provide useful data to such evaluations. In this study, it was aimed to develop a new and reliable instrument that is easily prepared by low cost for measuring inclinations of the face which can be measured by costly commercial tools. Materials and Methods: This instrument was made with adding appropriate pieces to a transparent ruler, calibrated and named as "inclinometer". In order to test the reliability of the inclinometer, a paired t test was used to compare differences between the measures taken from 30 men aged 18-25 years by using inclinometer and another commercial tool. Results: It was determined that inclinometer can be used in a number of inclination measurements of the face. No statistically significant differences were found between the measurements taken for comparison purpose (p>0.05). Conclusion: It is suggested that this new developed anthropometric instrument can be utilized in anthropometric studies and clinical evaluations, due to its simple and low-cost construction.©2005, Fırat Üniversitesi, Tıp Fakültesi

Amaç: Antropometri, şekil bozukluğu olan yüzlerin değerlendirilmesinde önemli bir yöntem olarak kabul edilir. Bu tip değerlendirmelerde eğim ölçümleri yararlı veri sağlar. Bu çalışmada, maliyeti yüksek ticari nitelikli aletler ile ölçülebilen yüz eğimlerinin ölçümlerinde kullanılmak üzere yapımı kolay, maliyeti çok düşük, güvenilir yeni bir alet geliştirilmesi amaçlandı. Gereç ve Yöntem: Şeffaf bir iletkiye amaca uygun parçalar eklenerek oluşturulan bu ölçüm aletinin kalibrasyonu yapıldı ve "Eğim Ölçer" adı verildi. Eğim Ölçer'in güvenilirliğini sınamak için, 18-25 yaş grubundaki 30 erkek üzerinde, eğim ölçer ve ticari nitelikli başka bir aletle yapılan ölçümler, eşleştirilmiş t testi ile karşılaştırıldı. Bulgular: Eğim Ölçer'in, yüz üzerinde çok sayıda eğim ölçümünde kullanılabileceği belirlendi. Karşılaştırma amaçlı yapılan ölçümler arasında, istatistiksel olarak anlamlı bir fark bulunmadı (p>0.05). Sonuç: Yeni geliştirilen bu antropometrik aletin, yapımının kolay ve düşük maliyetli oluşu, pratik kullanımı ve güvenilirliği ile antropometrik çalışmalar ve klinik değerlendirmelerde yer bulacağı düşünüldü.©2005, Fırat Üniversitesi, Tıp Fakültesi
Yüzün Eğim Ölçümleri İçin Yeni Bir Antropometrik Alet ve Güvenilirliği